Prevalence of cataracts in Iran based on the Persian eye cohort study - Fateme Alipour; Parisa Abdi; Hassan Asadigandomani; Mehran Rezakhani; Fatemeh Moosaie; Fateme Jafari; Mehdi Yaseri; Nazgol Motamed-Gorji; Fahimeh Khalili; Roya Tavakoli; Abolfazl Tahkor; Masoome Mohseni; et al. (Scientific Reports)
Abstract The PERSIAN eye cohort study is a population-based study that evaluates the overall prevalence of cataracts and their subtypes (nuclear sclerosis, cortical, and PSC) in Iran. In this study, from January 2015 to September 2021, 16,016 participants over 35 years of age from four provinces who were selected by random cluster sampling were examined. Demographic information, education, socioeconomic status, and place of residence were collected through interviews. The cataract status of the study participants was examined by two experienced ophthalmologists using slit lamp photography. The average age of the study participants was 49.52 ± 9.31 and 8891 (55.5%) were female. The overall prevalence of each type of cataract, nuclear sclerosis, cortical, and PSC was 18.90%, 12.65%, 9.20%, and 3.08%, respectively. The results indicated that the prevalence of any type of cataract (adjusted OR = 0.85, 95% CI: 0.78–0.92, p < 0.001) and NS cataract (adjusted OR = 0.80, 95% CI: 0.73–0.88, p < 0.001) is lower in women. The risk of developing cataracts increased exponentially with aging. The prevalence of any type of cataract and cortical subtype was higher in rural than urban populations. Also, the risk of developing cataracts decreased with an increase in education level and socioeconomic status and some Iranian races such as Arabs, Azari, and Guilak were also at a higher risk of cataracts. The results of this study indicate the importance of a comprehensive regard of cataract as one of the causes of avoidable blindness in Iran due to its higher prevalence than the global average.